Nancy Drew mystery stories 14 the whispering statue - CAROLYN KEENE (New York Grosset & Dunlap, 1970)
Nancy Drew investigates a stolen marble statue that (3z(Bwhispers(3y (Band looks like her while also uncovering a dishonest art dealer$1 (Bs schemes.s
English